Continuous cultivation of Dehalococcoides mccartyi with brominated tyrosine avoids toxic byproducts and gives tight reactor control. (1st February 2023) - Reino, Clara; Ding, Chang; Adrian, Lorenz
Highlights: 3, 5-Dibromotyrosine was used for biomass production of Dehalococcoides. A continuous lab reactor led to stable cultivation of planktonic Dehalococcoides. Pressure decrease due to hydrogen consumption enabled online activity monitoring. The reductive dehalogenase CbdbA238 was specifically induced by dibromotyrosine. Abstract: Dehalococcoides mccartyi strain CBDB1 is a strictly anaerobic organohalide-respiring bacterium with strong application potential to remediate aquifers and soils contaminated with halogenated aromatics. To date, cultivation of strain CBDB1 has mostly been done in bottles or fed-batch reactors. Challenges with such systems include low biomass yield and difficulties in controlling the growth conditions. Here, we report the cultivation of planktonic D. mccartyi strain CBDB1 in a continuous stirring tank reactor (CSTR) that led to high cell densities (∼8 × 10 8 cells mL -1 ) and dominance of strain CBDB1. The reactor culture received acetate, hydrogen, and the brominated amino acid D- or L-3, 5-dibromotyrosine as substrates. Both D- and L-3, 5-dibromotyrosine were utilized as respiratory electron acceptors and are promising for biomass production due to their decent solubility in water and the formation of a non-toxic debromination product, tyrosine. By monitoring headspace pressure decrease which is indicative of hydrogen consumption, the organohalide respiration rate was followed in real time. Proteomics analyses revealed that the reductive dehalogenase CbdbA238 was highly expressed with both D- and L-3, 5-dibromotyrosine, while other reductive dehalogenases including those that were previously suggested to be constitutively expressed, were repressed. Denaturing gradient gel electrophoresis (DGGE) of amplified 16S rRNA genes indicated that the majority of cells in the community belonged to the Dehalococcoides although the CSTR was operated under non-sterile conditions. Hence, tightly controlled CSTR cultivation of Dehalococcoides opens novel options to improve biomass production for bioaugmentation and for advanced biochemical studies. Graphical abstract: Image, graphical abstract